Mother’s Compliance in Providing Basic Immunization for Infants Aged 0–12 Months - Teresia Hemelka; Blacius Dedi; Atik Badi’ah (Newinera Publisher, 2025)
Basic immunization is an important health intervention to prevent dangerous infectious diseases in infants. However, the coverage of basic immunization in Sungai Raya Village, Pinoh Utara Sub-District, Melawi Regency, West Kalimantan Province is still low, at only 67.8%, far below the national target of 95%. The low compliance of mothers in providing basic immunization is influenced by various internal and external factors. This study aims to explore mothers’ experiences in complying with basic immunization for infants aged 0–12 months, as well as to identify the supporting and inhibiting factors of such compliance. This research used a qualitative method with a phenomenological approach. Informants were selected using purposive sampling, namely mothers who have infants aged 0–12 months and who reside in Sungai Raya Village. Data were collected through in-depth interviews using an interview guide, and were then analyzed thematically. The study revealed several main themes, namely: Mothers' Perceptions of Disease Risk and Immunization Benefits; Level of Compliance and Mothers' Experience in Immunization; Barriers in Fulfilling Basic Immunization; Supporting Factors for Mother’s Compliance; and the Influence of Social Environment and Information. Compliance with basic immunization is influenced by a complex interaction between internal factors (knowledge, attitude, beliefs) and external factors (family support, access to health services, culture). Community-based interventions are needed to strengthen health education, improve service access, and involve community leaders to overcome cultural barriers.